2000
DOI: 10.1073/pnas.060024897
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Correlation of enterohemorrhagic Escherichia coli O157 prevalence in feces, hides, and carcasses of beef cattle during processing

Abstract: A survey was performed to estimate the frequency of enterohemorrhagic Escherichia coli O157:H7 or O157:nonmotile (EHEC O157) in feces and on hides within groups of fed cattle from single sources (lots) presented for slaughter at meat processing plants in the Midwestern United States, as well as frequency of carcass contamination during processing from cattle within the same lots. Of 29 lots sampled, 72% had at least one EHEC O157-positive fecal sample and 38% had positive hide samples. Overall, EHEC O157 preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(71 citation statements)
references
References 10 publications
1
69
1
Order By: Relevance
“…E. coli O157 is present in cattle at the prevalence ranging from 0% to 61% [3]; however, the prevalence of this pathogen at NEFREC farm was 40.66% (37 of 91 cattle). Furthermore, when we investigated the prevalence of E. coli O157 from grazing cattle at the same farm (i.e., NFREC), prevalence of this pathogen was 1.1% (1 out of 91 animals; Oh and Jeong’s unpublished data).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…E. coli O157 is present in cattle at the prevalence ranging from 0% to 61% [3]; however, the prevalence of this pathogen at NEFREC farm was 40.66% (37 of 91 cattle). Furthermore, when we investigated the prevalence of E. coli O157 from grazing cattle at the same farm (i.e., NFREC), prevalence of this pathogen was 1.1% (1 out of 91 animals; Oh and Jeong’s unpublished data).…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of Escherichia coli O157 in cattle herds (ranging 0–61%) [1], [2], [3], [4] is positively correlated to outbreaks of this pathogen causing severe diseases including hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS), which can cause kidney failure and be fatal [3], [5]. Despite the implementation of government regulations and development of process interventions, food recalls and human illness related to E. coli O157 remain concerns around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in some locations indicated increased prevalence of E. coli O157:H7 in cattle in warmer months of the year, which may correlate with a seasonal variation in contamination of raw milk (Brown, Harmon, Zhao, & Doyle, 1997;Chapman, Siddons, Cerdan Malo, & Harkins, 1997). For example, a U.S. study revealed that a higher prevalence of E. coli O157:H7 in beef cattle presented for slaughter from July to August 1999 than other months (Elder et al, 2000).…”
Section: Occurrence Of E Coli O157:h7 In the Factoriesmentioning
confidence: 99%
“…Although many food and dairy products have acted as vectors, the majority of reported cases appear to be attributed to the consumption of foods of bovine origin; with ground beef the most frequently identified vehicle (2). Cattle comprise a main reservoir of O157 and this organism can be found in their feces, rumen, hide, and derived carcasses (3–5). Foodborne disease and product recalls because of this organism continue to occur even though control measures have been under investigation for over 20 years (6).…”
mentioning
confidence: 99%